Potential Therapeutic Strategy for EGFR-Mutant Lung Cancer With Concomitant EML4-ALK Rearrangement—Combination of EGFR Tyrosine Kinase Inhibitors and ALK Inhibitors - Ming-Hung Huang, PhD; Jih-Hsiang Lee, MD; Pei-Shan Hung, PhD; James Chih-Hsin Yang, MD, PhD (JTO Clinical and Research Reports, 2022)
Introduction: Although driver gene mutations have been believed to be mutually exclusive, some patients with NSCLC and concomitant EGFR mutations and EML4-ALK rearrangements have been reported. In this study, we reported a case of a patient with lung cancer who harbored both EGFR mutation and the EML4-ALK rearrangement after acquiring resistance to the EGFR tyrosine kinase inhibitor treatment. EGFR-mutant and ALK fusion proteins were detected in the same tumor cells through immunohistochemical analysis. Investigation of the molecular mechanisms of concomitant EGFR mutation and the EML4-ALK rearrangement in the same tumor cell can help discover an appropriate treatment for these patients. Methods: PC-9 cells, expressing EGFR exon 19 deletion, were transfected with EML4-ALK variant 3a (v3a) and variant 3b (v3b) separately and selected, and the effect of EGFR and ALK inhibitors was evaluated in vitro and in vivo. Results: PC-9_v3a-gef and PC-9_v3b-gef cells were resistant to gefitinib and ALK inhibitors alone, but ALK inhibitors enhanced gefitinib-induced cytotoxicity. In animal studies, gefitinib completely inhibited the tumor growth in PC-9_vector cells but not in PC-9_v3a-gef and PC-9_v3b-gef cells. A combination of ALK inhibitor and gefitinib was found to be more potent than gefitinib alone in PC-9_v3a-gef and PC-9_v3b-gef cells. Furthermore, combination treatment with osimertinib and ceritinib caused a decrease in liver tumor size of the patient with liver metastases. Conclusions: Our data suggest that combination treatment with EGFR and ALK inhibitors can be a therapeutic strategy for treating NSCLC with concomitant EGFR mutation and EML4-ALK rearrangement.